Hubungan Pengetahuan Dan Budaya Dengan Tindakan Pemanfaatan Kelor Di Kabupaten Sumba Timur - Maria Kareri Hara; Yuneti Octavianus Nyoko (Poltekkes Kemenkes Kupang, 2020)
Background: Moringa leaves are a fairly good alternative in meeting the nutritional needs of underweight toddlers, pregnant women with anemia and in daily life and can be used as a business with high economic value. The purpose of this study is correlation between of knowladge and cultural with intervention of using Moringa as a food ingredient for improving family nutrition. Method: Cross-sectional design analytic study. Sample are 399 family from Lewa and Pandawai sub-districts. The dependent variable of this study is the intervention of using Moringa and the independent variables study are knowledge and culture of Moringa. The instrument used is a questionnaire. The statistic analisis of study is chi squere. Results: Bivariate analysis is good knowledge related 18 times to Moringa utilization measures (PR = 18,389; 95% CI = 9,722-34,784; p-value <0,001), good culture relates 5 times to Moringa utilization measures (PR = 4,698; 95% CI = 2,631-8,391; p-value <0,001). Conclusion : There is a significant relationship between knowledge and culture with the use of Moringa utilization measures. Latar Belakang: Daun kelor merupakan alternatif yang cukup baik dalam pemenuhan kebutuhan gizi balita kurus, ibu hamil dengan anemia maupun dalam kehidupan sehari-hari serta dapat dijadikan usaha yang bernilai ekonomis tinggi. Tujuan penelitian untuk melihat hubungan pengetahuan dan budaya dengan tindakan pemanfaatan kelor di Kabupaten Sumba Timur. Metode: Studi analitik desain crosssectional. Jumlah sampel 399 kepala keluarga dari Kecamatan Lewa dan Pandawai. Variabel terikat penelitian ini adalah tindakan pemanfaatan kelor dan variabel bebas yang diteliti adalah pengetahuan dan budaya. Instrumen yang digunakan yaitu kuesioner. Analisis statistik yang digunakan adalah chi squere. Hasil: Hasil analisa statistik menunjukkan terdapat hubungan antara pengetahuan dengan tindakan pemanfaatan daun kelor (PR=18,389;95%CI=9,722-34,784; p-value <0,001) dan terdapat hubungan budaya dengan tindakan pemanfaatan kelor (PR=4,698;95%CI=2,631-8,391; p-value <0,001). Kesimpulan : Terdapat hubungan yang cukup signifikan antara pengetahuan dan budaya dengan tindakan pemanfaatan daun kelor.